Case report of 18F–fluorodeoxyglucose positron emission tomography‐computed tomography imaging of a patient with multiple endocrine gland metastases from small cell lung cancer. Issue 1 (5th October 2017) - Zhao, Hongguang; Lin, Chenghe; Jiao, Benzheng; Sa, Ri; Hou, Sen; Xu, Songbai
Abstract : Synchronous multiple endocrine gland metastasis caused by small cell lung cancer (SCLC) is rare. A patient was investigated for primary cancer because of suspected brain metastasis on computed tomography (CT). Baseline 18 F–fluorodeoxyglucose (FDG) positron emission tomography (PET)‐CT was positive in the lung and multiple endocrine glands (right thyroid, right breast, pancreatic body, right adrenal gland, and left ovary). Histopathology confirmed small cell lung cancer. The patient's symptoms were alleviated after chemotherapy and brain radiotherapy. Follow‐up PET‐CT revealed that some of the lesions had disappeared and some had reduced in size. This rare case of multiple endocrine gland metastases from SCLC suggests that whole body PET‐CT is a useful tool to detect rare/asymptomatic metastases.